Neuropharmacological, Antidiarrheal, and Antimicrobial Effects of Chaetomorpha aerea Acetone Extract: GC-MS Profiling and In Silico Analysis - Md. Mahmudul Hasan; Md. Safayat Hossen Momen; Md. Abdul Alim; Sajjad Hossen Chowdhury; Miton Chowdhury; Md Al Mamun; Fatema Tuz Zohra; Md. Jakaria Parvez; Suman Das; S. M. Moazzem Hossen (Scientifica)
Chaetomorpha aerea, distributed in temperate and tropical coastal regions, is traditionally consumed as a nutrient-rich food source in coastal communities and is believed to possess medicinal properties. This study evaluated the sedative, anxiolytic, antidiarrheal, and antimicrobial activities of the acetone extract of C. aerea (AECA). Furthermore, GC-MS performed a quantitative phytochemical analysis of the AECA. Sedative activity was evaluated in mice using the open field test (OFT) and hole cross test (HCT); anxiolytic activity was assessed using the elevated plus maze (EPM), hole board test (HBT), and light–dark box test (LDBT); and antidiarrheal activity was determined through castor oil–induced diarrhea and gastrointestinal motility test. The disc-diffusion method was employed to evaluate antibacterial activity. In both OFT and HCT models, AECA 400 mg/kg demonstrated a significant reduction of square crossed and hole crossed compared to diazepam, respectively. In the case of EPM and HBT, 400 mg/kg dose of AECA demonstrated significant dose-dependent activity. Both in the castor oil–induced diarrhea and gastrointestinal motility test, 400 mg/kg of AECA demonstrated moderate inhibition of diarrhea compared to standard loperamide. Antimicrobial assay of AECA showed considerable inhibition against Escherichia coli and Salmonella typhi, measuring inhibition zones of 14 mm and 13 mm. Bioactive metabolites from GC-MS analysis were investigated through molecular docking. Docking was performed against GABAA receptor (6X3T), MAO-A (2Z5X), M3 muscarinic receptor (5ZHP), E. coli FabI (1LX6), and GyrA (5ZTJ). AECA showed notable sedative, anxiolytic, antidiarrheal, and antimicrobial activities. To evaluate the molecular pathways involved and isolate the bioactive ingredients, more research is required.